Recent Advances in the Development of Environmentally Benign Treatments to Control Root-Knot Nematodes - Forghani, Fereidoun; Hajihassani, Abolfazl (Frontiers in Plant Science, 2020)
Root-knot nematodes (RKNs), Meloidogyne spp., are sedentary endoparasites that negatively affect almost every crop in the world. Current management practices are not enough to completely control RKN. Application of certain chemicals is also being further limited in recent years. It is therefore crucial to develop additional control strategies through the application of environmentally benign methods. There has been much research performed around the world on the topic, leading to useful outcomes and interesting findings capable of improving farmers’ income. It is important to have dependable resources gathering the data produced to facilitate future research. This review discusses recent findings on the application of environmentally benign treatments to control RKN between 2015 and April 2020. A variety of biological control strategies, natural compounds, soil amendments and other emerging strategies have been included, among which, many showed promising results in RKN control in vitro and/or in vivo. Development of these methods continues to be an area of active research, and new information on their efficacy will continuously become available. We have discussed some of the control mechanisms involved and suggestions were given on maximizing the outcome of the future efforts.